IS CONSUMER LOYALTY JUDGING FROM THE CAFE ATMOSPHERE AND THE CONFORMITY OF THE TASTE OF THE PRODUCT? - Melisa Riskawati; Riza Bahtiar Sulistyan; Ninik Lukiana (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2021)
Currently the development of the coffee shop industry is increasing. This phenomenon is also seen in Lumajang City. Cafes or coffee shops are in great demand by business people, so many cafes appear every year, one of which is GA Cafe Lumjang.The solution offered in this phenomenon is by develop appropriate marketing strategies such as atmosphere and product taste suitability to maintain customer loyalty. This study aims to determine the effect of cafe atmosphere and product taste suitability on consumer loyalty at GA Cafe Lumajang partially. The research method used is a quantitative research method with multiple linear regression analysis techniques. The number of samples in this study were 94 respondents. The research was carried out by spreadingquestionnaire to consumers GA Cafe Lumajang. The results of this study indicate that cafe atmosphere and product taste suitability have a significant effect on consumer loyalty with a coefficient of determination of 35.4%, the remaining 64.6% of consumer loyalty can be influenced by other variables such as location, service, promotion and product diversity.